Q. 94.6( 8 Votes )

<span lang="EN-US

Answer :

= x2 – xz + xy – yz


= x(x – z) +y(x – z) (taking x and y as common resp.)


= (x + y)(x – z).

Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

Factorize each ofRD Sharma - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

10p2 +RS Aggarwal - Mathematics

7x2 - RS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics

<span lang="EN-USRS Aggarwal - Mathematics